(untitled) (Medical Forum Monthly, 2023)
Objective: The objective of the study entail to establish an evidence in Pakistani population regarding splenoportal-index as a diagnostic tool for the non-invasive detection of esophageal varices; a cost-effective and useful tool to screen patients in advance who are at high risk to bleed. Study Design: Prospective cross-sectional study. Place and Duration of Study: This study was conducted at the University Tertiary-care Hospital; conducted from December-2019 to June-2020. Materials and Methods: Eighty (N=80) male and female subjects (30-80 years) were selected in the study based upon clinical and laboratory evidence of liver-cirrhosis. Ethical approval for the study has been taken. Endoscopy was performed in Department of Medicine. Ethical issues were considered and complied. Splenic-index results found by ultrasonography and portal-vein velocity were correlatively compared with the outcomes of endoscopy. True positive, true negative, false positive, false negative patients were segregated. Data was analyzed by SPSS-20 by keeping p-value <0.05; a significant. Results: Male: Female ratio was 53(66%):27(34%). Subjects positive on Ultrasonography = 61 (76.25%) and positive on Endoscopy = 62 (77.50%) significantly correlated (p=0.001). Test sensitivity (92%); specificity (78%); positive-predictive-value (93%); negative-predictive-value (74%); accuracy (89%); false-positive-rate (22%) and false-negative-rate (8.0%). Conclusion: Ultrasonography is significantly accurate non-invasive; cost-effective and useful tool for the identification of varices of esophagus in patients suffering from liver-cirrhosis.